Vietnam Workforce Development : SABER Country Report 2012 - World Bank (Washington, DC, 2014)
Since Vietnam launched its economic reforms in 1986, the country has enjoyed more than two decades of rapid economic growth with concomitant reductions in poverty. In the coming years, as Vietnam looks to strengthening its global competitiveness and sustaining its record of rapid growth, it faces critical challenges. Poor labor market outcomes and low productivity remain important concerns that stem in part from the paucity of job-relevant skills among workers and the limited opportunities for workers to acquire or enhance their skills. The government s response to these challenges is encapsulated in two key documents which align closely with the country s Strategy for Socioeconomic Development approved by the National Assembly. The first is the Human Resource Development (HRD) Strategy (2011 2020), approved in 2011, which defines strategic targets for workforce development and offers guidance and solutions to meet the targets. The second document, the Vocational Training Development (VTD) Strategy (2011 2020), approved the following year, sets forth a roadmap for achieving specific targets in vocational education and training (VET).